PERANCANGAN INVERTER MASTS DENGAN MONITORING KECEPATAN MENGGUNAKAN SENSOR HALL BERBASIS ARDUINO - Mhd Ikbar; Zulwisli Zulwisli (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The use of Brushless Direct Current Machines (MASTS) is very much applied in the industrial world compared to other types of drive engines. For the MASTS drive a three-phase inverter is needed, a three-phase inverter is a circuit that is used to convert DC voltage into AC voltage with a certain frequency. The system used to control the inverter is to use Pulse Width Modulation (PWM), where the pulse width is used to regulate the speed. To optimize the MASTS rotation speed, it is necessary to make speed monitoring to determine the stability of the MASTS speed, so design is carried out by combining the monitoring of the MASTS speed with a three-phase inverter. This tool uses a hall sensor, Arduino, and liquid crystal display (LCD) display. The working principle of the hall sensor is detecting the rotation speed of the MASTS based on the working principle of the electromagnetic hall sensor. In this study, 5 variations of PWM potentiometer inputs 20%, 40%, 60%, 80%, 100% were used to determine the results of monitoring of the MASTS speed for each input variation. In this study, an error rate of 6.2% was observed.. Keywords: Sensor Hall, SMATS, Inverter, RPM